2010
DOI: 10.1021/jz101400d
|View full text |Cite
|
Sign up to set email alerts
|

Biradicaloid and Polyenic Character of Quinoidal Oligothiophenes Revealed by the Presence of a Low-Lying Double-Exciton State

Abstract: Evidence of the biradicaloid and polyenic character of quinoidal oligothiophenes is reported by proving at the CASSCF//CASPT2 computational level the presence of a low-lying double exciton state responsible for the weak features observed in the NIR absorption region of the longest members of this class of molecules. The energy lowering of this state, accompanying the length increase in the oligomers, causes a displacement of the ground-state equilibrium geometry toward more biradicaloid structures because of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
141
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(168 citation statements)
references
References 47 publications
24
141
1
2
Order By: Relevance
“…The most salient experimental features of a PAH with biradical character include the line broadening of 1 H NMR arising from the existence of thermally excited triplet species, and a relatively small HOMO-LUMO gap to facilitate doubly excited electronic configuration into the ground state configuration. 1,40 However, in contrast to the theoretical predictions, all functionalized stable hexacene and heptacene derivatives display 1 H NMR signals with sharp splitting and narrow line widths, indicating a closed-shell ground state. [41][42][43][44] Alternatively, investigations on nonacene derivatives provide promising observations which may arise from their singlet open-shell ground state (Fig.…”
Section: Higher Order Acenescontrasting
confidence: 61%
“…The most salient experimental features of a PAH with biradical character include the line broadening of 1 H NMR arising from the existence of thermally excited triplet species, and a relatively small HOMO-LUMO gap to facilitate doubly excited electronic configuration into the ground state configuration. 1,40 However, in contrast to the theoretical predictions, all functionalized stable hexacene and heptacene derivatives display 1 H NMR signals with sharp splitting and narrow line widths, indicating a closed-shell ground state. [41][42][43][44] Alternatively, investigations on nonacene derivatives provide promising observations which may arise from their singlet open-shell ground state (Fig.…”
Section: Higher Order Acenescontrasting
confidence: 61%
“…One signature of the diradicaloid character is the presence of a low-lying excited singlet state dominated by the doubly excited (H,H¡L,L) electronic configuration. 18 The S 0 ¡S 1 transition is one-photon forbidden but two-photon allowed, and as a consequent, a weak absorption shoulder is observed at low energy edge in open-shell singlet diradicaloids, and these molecules usually show large two-photon absorption (TPA) crosssections. Experimentally, the diradical character index can be evaluated if both one-photon and two-photon absorption spectra can be completely measured and the singlet-triplet energy gap can be determined:…”
Section: Renaissance Of Zethrene Chemistrymentioning
confidence: 99%
“…Negri et al reported that a weak low-energy band was observed for thienoquinoid compounds with large biradical character. 59 The reason why bisanthene has negligible biradical character while that of teranthene is appreciable is as follows. Upon transforming from the Kekulé to the biradical form for anthenes, one CC π-bond is cleaved, as shown in Figure 14.…”
Section: ¹1mentioning
confidence: 99%